Angioinvasive cerebral aspergillosis presenting as acute ischaemic stroke in a patient with diabetes mellitus - Mohamed Ibrahim, Norlinah; Ngow, Harris Abdullah; BB, Hamidon (Singapore Medical Association, 2007)
Cerebral angioinvasive aspergillosis is a rare manifestation of disseminated aspergillosis which may result in stroke in immunocompromised individuals. Reports of such disease in patients with diabetes mellitus are rare. We describe a 45-year-old man with diabetes mellitus who presented with a three-day history of right-sided limb weakness and aphasia. Cerebral computed tomography showed features of an acute infarct involving the left anterior and middle cerebral arteries. He was initially treated for an acute ischaemic stroke. Further history revealed that he was investigated for a growth in the sphenoid sinus two months earlier. Culture of the biopsied material from the sphenoid sinus grew Aspergillus fumigatus. Magnetic resonance imaging showed an extension of the growth to the brain, causing the acute ischaemic stroke. He was subsequently diagnosed with angioinvasive cerebral aspergillosis and was commenced on intravenous amphotericin B. Unfortunately, he succumbed to his illness despite treatment.